Od profesionalizma do "odmevne komore" - Mance, Boris (Javnost (Ljubljana), 2014)
Studies of political communication on Twitter which focus on the relationships between politicians and journalists are rare; moreover, they neglect the importance of mutual retweeting (when politicians retweet messages of journalist and vice versa). This study examines these relations through the prism of mutual granting of relevance and communicative roles that are being taken over. Analysis of this relationship involves three methods: by network analysis we identify four communication samples regarding granting of relevance through retweeting among journalists and politicians: coalition, traditional, control and individual communication pattern. These are then combined with interviews done with key players that have been identified in these patterns. By analysing quantitatively the content of attributions to the original message, we investigate the nature that it reflects and categorise them by mediative, advocative, critical, entertaining or communitarian communicative roles that actors are undertaking. The study notes two distinct patterns regarding granting of relevance via Twitter: coalition pattern, in which the politicians of a certain party and journalists of certain media outlets form an alliance when granting relevance and exclude dissident actors which indicates a tendency towards a formation of "echo chamber". On the other hand, the survey also identifies a traditional pattern, which shows a marked absence of players of other political parties and mainstream print media in practices of such kind, reflecting the preservation of boundaries between the two groups. The survey also finds that the actors when retweeting assume intermediary roles and very rarely modify the content of the original message.
Keywords: politična propaganda; politična kampanja; communication; komuniciranje; mass media; množični mediji; družbena omrežja; socialna omrežja